Peran Pengawasan Internal Dalam Menghindari Kutukan Sumber Daya Alam - Andilo Tohom (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
Indonesia is one of many countries in the world so called resource-rich country. Natural resources abundance needs to be managed in the right way in order to avoid dutch diseases and resources curses. These two phenomena generally happened in the country, which has abundant natural resources. Learned from Norwegian experiences, Indonesian Government need to focus its policy to prevent rent seeking activities. The literature study presented in this paper is aimed to provide important insight for government entities in focusing their policies and programs to avoid resources curse. From the internal audit perspective, this study is expected to improve internal audit’s role in assurance and consulting.